Defining the System and Plan Drafting Process for the Waste Management. (2015) - Šerifi, Veis; Tarić, Mirsad; Milojević, Ivan; Milosavljević, Milutin
Abstract: In this paper, consideration will be given to defining the system and development of a plan for solid municipal waste management. The initial steps are reflected in forming a group for developing the plan including partnerships of all interested actors. The planning period and any restrictions on the planning process are defined. The factors affecting the definition are discussed. All existing plans and mutual interactions are taken into consideration. The data as well as the information on the current situation are obtained and analyzed data and the condition evaluation is performed. Defining the system is a complex task that should be left to experts and competent individuals and organizations, in order to reduce the risk of wrong definition